Ectopic Expression of the Allium cepa 1-SST Gene in Cotton Improves Drought Tolerance and Yield Under Drought Stress in the Field - Liu, RuiNa; Jiao, TianQi; Zhang, ZeXing; Yao, Zhang; Li, ZhongQing; Wang, Saisai; Xin, Hongliang; Li, YuXia; Wang, AiYing; Zhu, JianBo (Frontiers in Plant Science, 2022)
In some plants, sucrose: sucrose 1-fructosyltransferase (1-SST) is the first irreversible key enzyme in fructan biosynthesis. Studies have shown that fructan accumulation enhances abiotic stress tolerance of plants. To investigate the role of 1-SST in drought stress responses, a total of 37 cotton plants expressing a 1-SST gene from Allium cepa were developed by Agrobacterium-mediated transformation. Under drought stress in the field, compared with wild-type, ectopic expression of Ac1-SST in cotton resulted in significantly higher soluble sugars (especially 1-kestose), proline and relative water contents (RWC), as well as decreased malondialdehyde (MDA) content, which contributed to maintaining intracellular osmoregulation and reducing membrane damage. In addition, ectopic expression of Ac1-SST in cotton significantly improved the photosynthesis rate, performance of PSII (including Pn, Fv/Fm, WUE, ΦPSII and PItotal) and plant growth under drought stress. Furthermore, compared with the wild type, under the droughted field, the yield loss per square meter of transgenic cotton was reduced by an average of 20.9% over two consecutive years. Our results indicate that the Ac1-SST gene can be used to improve drought tolerance and yield of cotton varieties, and might also be a promising drought-resistant gene for improving other crop varieties.